2021
DOI: 10.3390/s21082594
|View full text |Cite
|
Sign up to set email alerts
|

Dataset of Tactile Signatures of the Human Right Hand in Twenty-One Activities of Daily Living Using a High Spatial Resolution Pressure Sensor

Abstract: Successful grasping with multi-fingered prosthetic or robotic hands remains a challenge to be solved for the effective use of these hands in unstructured environments. To this end, currently available tactile sensors need to improve their sensitivity, robustness, and spatial resolution, but a better knowledge of the distribution of contact forces in the human hand in grasping tasks is also necessary. The human tactile signatures can inform models for an efficient control of the artificial hands. In this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This can be observed in sensor activation in tasks A1, A3, and A4 (all requiring power grasps), where additional palm sensors detected grasp or release. These results are consistent with previous studies analyzing hand pressure distribution in activities of daily living [15]. The only important difference regarding the results in the literature was the inactivity observed for pressure sensor s10.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This can be observed in sensor activation in tasks A1, A3, and A4 (all requiring power grasps), where additional palm sensors detected grasp or release. These results are consistent with previous studies analyzing hand pressure distribution in activities of daily living [15]. The only important difference regarding the results in the literature was the inactivity observed for pressure sensor s10.…”
Section: Resultssupporting
confidence: 91%
“…The only important difference regarding the results in the literature was the inactivity observed for pressure sensor s10. This palm spot was observed to present a higher activation of pressure sensors in [15] but this may be attributable to the pressure sensor size, as the used in previous studies was almost thrice the size of VMG30 sensors. The second spot observed to have higher activation in the aforementioned study was distal phalanx of index finger, which is consistent with the results here obtained using VMG30. ))…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The expected force/pressure during pHRI with SARs can be a result of people touching, hugging, petting, and/or holding the robots or the robots actively initiating these behaviors. Tsetserukou et al [ 88 ] reported that human–human hugging can generate a pressure between 1.4 kPa and 5.9 kPa while Cepriá-Bernal et al [ 89 ] reported that human hand grasping can create pressure between 30 kPa and 270 kPa. As a result, soft pressure sensors would need to detect a minimum pressure range from 1.4 kPa to a maximum of 270 kPa.…”
Section: Soft Robotics: Towards “Soft” Actuation and Sensingmentioning
confidence: 99%
“…As such, it is understandable that considerable research effort has been put into measuring the exchanged actions between the hand and the manipulated object, with pressure being the most obvious target physical quantity. The most widespread sensing method is based on piezo-resistive pressure sensors [ 1 , 2 , 3 , 4 , 5 ], constituted by a matrix of sensing elements embedded in polymeric sheets. The method has proven its reliability and accuracy in countless applications and is the de facto industry standard.…”
Section: Introductionmentioning
confidence: 99%